(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The contemporary business environment is witnessing increasing calls for modifications to the traditional cost system, and a trend towards adopting cost management techniques to provide appropriate financial and non-financial information for senior and executive departments, including the Resource Consumption Accounting (RCA) technique in question, which classifies costs into fixed and variable to support the decision-making process. Moreover, (RCA) combines two approaches to cost estimation, the first based on activity-based cost accounting (ABC) and the second on the German cost accounting method (GPK). The research aims to provide a conceptual vision for resource consumption accounting, after Considering it as an accounting technique for cost management, working on the optimal exploitation of available resources and employment of idle energy to contribute to reducing the cost of products and enhancing competitiveness between units, as well as explaining its concepts, components, features and determinants of their application. Between the unit’s resources and outputs, in order to support senior management financially and materially. b Resisting change, which is attributed to lack of knowledge of application rules and policies on the one hand, and fear of failure to adopt cost management techniques. The researchers recommend the adoption of the proposed vision of technology in the Iraqi units to know the homogeneous resource pools, which will clarify the interconnected relationships between them and indicate the extent to which each resource directly benefits from the other, with the aim of knowing the path of the flow of energy costs, in order to reach the cost measurement as much as the resources used.